Influence of magnesium on excitability of neurons of different levels of their organization - S. A. Antonenko (Kazimierz Wielki University, 2019)
Abstract The article indicates that the hyper-excitability of neurons is associated with ionic imbalance of cell membranes, in which a number of trace elements are involved. The energy component of these processes is associated with the presence of magnesium (Mg) as a universal supplier of the latter. Mg supports the functioning of NMDA receptors, which does not allow the excitotoxic effects of glutamate, which triggers the mechanisms of Ca entry into the neuron and its death, to manifest itself. Mg stimulates the main excitatory neurotransmitter acetylcholine, regulates the release of serotonin, glycine, dopamine, thereby normalizing the extrapyramidal system, the spinal stem structures, and the final executive motor apparatus. Participates in the energy support of adaptation processes, the activation of central regulatory mechanisms, control the excess of catecholamines and corticosteroids, other hormones and mediators involved in stress reactions.